"Playing Hooky" Health Messages: Apprehension, Impression Management, and Deception. Issue 3 (4th March 2018) - Barrett, Ashley; Murphy, Melissa; Blackburn, Kate
ABSTRACT: This study investigates playing hooky in higher education classrooms and associates this behavior with students' communicative dispositions, instructor perceptions, and language use. We define "playing hooky" as students skipping class and explaining their absence to their instructor with deceptive health messages. The purpose of Study 1, an online survey ( N = 177 ), is to further understand the characteristics of students who engage in this type of deceptive health communication. Study 1 measures communication apprehension and perceived instructor credibility in students who had played hooky from class and those who had not. Findings reveal that students who communicate playing hooky health messages (a) reported more instructor communication apprehension and (b) perceived the instructors with whom they had played hooky to be less credible. Study 2 uses facework theory and MEH analysis to reveal the different linguistic strategies students use to communicate (a) truthful health messages ( N = 165) and (b) deceptive heath messages ( N = 82) to their instructor following an absence. Results demonstrate that students' facework strategies are more geared toward saving instructors' negative face in the deceptive health message condition. Implications of both studies are offered.